Ivarmacitinib reduces the need for adding/escalating medications in moderate-to-severe rheumatoid arthritis patients: a post hoc analysis from a phase III trial - Liu, Huaxiang; Li, Jie; Song, Lijun (Frontiers in Pharmacology, 2025)
BackgroundUncontrolled rheumatoid arthritis (RA) requires increasing the dosage of medications or adding combination therapies, leading to higher costs and increased risks of adverse events. This study aimed to assess the impact of ivarmacitinib, a selective Janus kinase 1 inhibitor, on the needs for adding/escalating medications in patients with moderate-to-severe RA.MethodsThis was a post hoc study from a phase III clinical trial (NCT04333771). Patients were randomized to receive ivarmacitinib 4 mg (n = 189), 8 mg (n = 189), or placebo (n = 188) until week 24 (W24). From W24 to W52, patients with placebo switched to ivarmacitinib 4 mg, while patients with ivarmacitinib continued the initial treatment. Adding/escalating medication was defined as an increased dosage or new medication addition for RA treatments (excluding the study drug).ResultsIvarmacitinib 4 mg (7.4%) and 8 mg (5.3%) groups had significantly lower rates of adding/escalating medication compared to the placebo group (22.3%) within W24 (both P < 0.001). Specifically, the ivarmacitinib groups presented lower rates of adding/escalating oral glucocorticoids (1.1% and 0.5%, versus 5.9%) and non-steroidal anti-inflammatory drugs (6.9% and 4.2%, versus 20.2%) than the control group within W24. No statistical significance was observed between groups in adding/escalating intravenous/intramuscular corticosteroids, conventional synthetic disease-modifying antirheumatic drugs, or systemic immunosuppressants. From W24 to W52, the rates of adding/escalating medications remained low in ivarmacitinib 4 mg (4.2%) and 8 mg (3.2%) groups; the switched group showed a reduced rate of adding/escalating medications (12.2%).ConclusionIvarmacitinib significantly reduces the need for adding/escalating medications compared to placebo, thereby potentially decreasing treatment burden. However, the post hoc, exploratory nature of this study requires further validation for the findings.